Regioselective One-Pot Synthesis of Hydroxy-(S)-Equols Using Isoflavonoid Reductases and Monooxygenases and Evaluation of the Hydroxyequol Derivatives as Selective Estrogen Receptor Modulators and Antioxidants - Song, Hanbit; Lee, Pyung-Gang; Kim, Junyeob; Kim, Joonwon; Lee, Sang-Hyuk; Kim, Hyun; Lee, Uk-Jae; Kim, Jin Young; Kim, Eun-Jung; Kim, Byung-Gee (Frontiers in Bioengineering and Biotechnology, 2022)
Several regiospecific enantiomers of hydroxy-(S)-equol (HE) were enzymatically synthesized from daidzein and genistein using consecutive reduction (four daidzein-to-equol–converting reductases) and oxidation (4-hydroxyphenylacetate 3-monooxygenase, HpaBC). Despite the natural occurrence of several HEs, most of them had not been studied owing to the lack of their preparation methods. Herein, the one-pot synthesis pathway of 6-hydroxyequol (6HE) was developed using HpaBC (EcHpaB) from Escherichia coli and (S)-equol-producing E. coli, previously developed by our group. Based on docking analysis of the substrate or products, a potential active site and several key residues for substrate binding were predicted to interpret the (S)-equol hydroxylation regioselectivity of EcHpaB. Through investigating mutations on the key residues, the T292A variant was verified to display specific mono-ortho-hydroxylation activity at C6 without further 3′-hydroxylation. In the consecutive oxidoreductive bioconversion using T292A, 0.95 mM 6HE could be synthesized from 1 mM daidzein, while 5HE and 3′HE were also prepared from genistein and 3′-hydroxydaidzein (3′HD or 3′-ODI), respectively. In the following efficacy tests, 3′HE and 6HE showed about 30∼200-fold higher EC50 than (S)-equol in both ERα and ERβ, and they did not have significant SERM efficacy except 6HE showing 10% lower β/α ratio response than that of 17β-estradiol. In DPPH radical scavenging assay, 3′HE showed the highest antioxidative activity among the examined isoflavone derivatives: more than 40% higher than the well-known 3′HD. In conclusion, we demonstrated that HEs could be produced efficiently and regioselectively through the one-pot bioconversion platform and evaluated estrogenic and antioxidative activities of each HE regio-isomer for the first time.